Impact of Intellectual Capital on Financial Performance of Firms : A Study on Tourism and Hospitality Firms in India - Kesse, Godfred Oppong; Irfan, Mohd.; Pattanayak, J. K. (Indian Journal of Finance, 2019)
This paper assessed the relationship existing between intellectual capital (IC) and financial performance of tourism and hospitality services firms in India. Data comprising of 720 firms were sourced from Prowess database for a period of 12 years. The study measured IC efficiency using the value added intellectual coefficient (VAIC) model developed by Pulic (2000). The study applied fixed and random effect models to account for differences (unobserved effects) across firms. The results confirmed the existence of a positive relationship between VAIC and performance of firms operating in the tourism and hospitality industry in India. Furthermore, unlike the dicey results of physical and structural capital, human capital was found to be the most influential component of IC, which had a significant impact on both return on assets and sales growth, suggesting that human capital is still the most important tool driving financial performance. Therefore, managers of such firms can manage their performance by investing in their human resources through training and development programs to enhance their skills needed to be more functional in this knowledge economy.